Women between Part-Time and Full-Time Work: The Influence of Changing Hours of Work on Happiness and Life-Satisfaction - Vanessa Gash; Antje Mertens; Laura Romeu Gordo (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
This paper asks whether part-time work makes women happy. Previous research on labour supply has assumed that as workers freely choose their optimal working hours on the basis of their innate preferences and the hourly wage rate, outcome reflects preference. This paper tests this assumption by measuring the impact of changes in working-hours on life satisfaction in two countries (the UK and Germany using the German Socio-Economic Panel and the British Household Panel Survey). We find decreases in working-hours bring about positive and significant improvement on well-being for women.
Keywords: J41; J64; I10; 330; Temporary Employment; Unemployment; Health; Teilzeitarbeit; Beschäftigungssystem; Weibliche Arbeitskräfte; Arbeitszeitgestaltung; Frauen; Zufriedenheit; Deutschland; Großbritannien